2016
DOI: 10.1016/j.jprot.2016.04.023
|View full text |Cite
|
Sign up to set email alerts
|

The effects of PPO activity on the proteome of ingested red clover and implications for improving the nutrition of grazing cattle

Abstract: Increasing the rumen-stable protein content of feed would lead to improved nitrogen utilisation in cattle, and less nitrogenous waste. Red clover (Trifolium pratense L.) is a high protein ruminant feed containing high polyphenol oxidase (PPO) activity. PPO mediated protein-quinone binding has been linked to protecting plant proteins from proteolysis. To explore the mechanism underlying the effect of PPO on protein protection in fresh forage feeds, proteomic components of feed down-boli produced from wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…It was more likely to be influenced by the PPO‐mediated proteolytic inhibition in red clover. The role of PPO in reducing proteolysis has been well demonstrated by numerous studies (Hart, Onime, Davies, Morphew, & Kingston‐Smith, ; Sullivan & Hatfield, ). The proposed mechanism of PPO‐reduced proteolysis is through the generation of o ‐quinones that react with nucleophilic sites on cellular proteins, reforming a phenol covalently bound to protein.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It was more likely to be influenced by the PPO‐mediated proteolytic inhibition in red clover. The role of PPO in reducing proteolysis has been well demonstrated by numerous studies (Hart, Onime, Davies, Morphew, & Kingston‐Smith, ; Sullivan & Hatfield, ). The proposed mechanism of PPO‐reduced proteolysis is through the generation of o ‐quinones that react with nucleophilic sites on cellular proteins, reforming a phenol covalently bound to protein.…”
Section: Discussionmentioning
confidence: 90%
“…The proposed mechanism of PPO‐reduced proteolysis is through the generation of o ‐quinones that react with nucleophilic sites on cellular proteins, reforming a phenol covalently bound to protein. Proteolysis thus is reduced either directly, by effective inhibition of proteases, or a reduction in general protein solubility through protein–phenol binding (Hart et al., ). This PPO‐mediated protein protection is only effective for a limited time post‐sealing because of its oxygen dependence (Lee, Scott, Tweed, Minchin, & Davies, ).…”
Section: Discussionmentioning
confidence: 99%
“…Breeding in North America has also reduced the drying time of RC forage by removing its stem hairs (Taylor, 2008b), and incorporation of this into other breeding programs, particularly in areas in which drying times are problematic, may alleviate this concern. Increased expression of polyphenol oxidase (PPO) should also be a key breeding target, as PPO activity in ensiling inhibits proteolysis, enhancing N-use efficiency in ruminants and reducing losses in excreta (Hart et al, 2016). The forage value of new varieties is further increased by im-provements in persistence, as these can produce high protein yields for over three years (Marshall et al, 2017), which requires consistent amounts of N from BNF, ultimately contributing to soil fertility.…”
Section: Economic Considerationsmentioning
confidence: 99%
“…The rumen can be considered to be a semi-continuous flow fermenter in which the microbial consortium degrades the ingested feed, the products of which such as volatile fatty acids (VFA) and protein breakdown products are used to drive microbial growth (Huws et al, 2018). Flow-through of rumen liquor containing a proportion of the microbiota and nondegraded plant protein (Hart, Onime, Davies, Morphew, & Kingston-Smith, 2016) from the rumen to the small intestine allows absorption of nutrients into the animal's bloodstream driving animal productivity (Firkins, 1996). It has previously been demonstrated that endogenous plant enzymes responses to rumen conditions could contribute to inefficient protein use during fermentation by the rumen microbiota (Beha, Theodorou, Thomas, & Kingston-Smith, 2002;Kingston-Smith, Davies, Edwards, Gay, & Mur, 2012;Kingston-Smith, Merry, Leemans, Thomas, & Thoeodorou, 2005).…”
Section: Introductionmentioning
confidence: 99%